When in Doubt, Ask the Audience: Potential Users' Perceptions of Internet-Delivered Cognitive Behavioural Therapy for Chronic Pain - Luke H Schneider; Heather D Hadjistavropoulos (Pain Research and Management)
BACKGROUND: Although research has demonstrated that Internet-delivered cognitive behavioural therapy (ICBT) for chronic pain helps with adjustment to pain, it remains unclear how this treatment option would initially be perceived by individuals with chronic pain.